A pesca de arrasto de camarões no Povoado Pontal do Peba, Piaçabuçu, Alagoas - Brasil: aspectos socioeconômicos e ambientais. - Calazans, Elíne Monteiro (2023)
Shrimp play an extremely important role as fishery resources in the communities where they are present. In the Northeast region of Brazil, shrimp fishing is predominantly carried out by artisanal fishermen at different scales, and has a significant relevance in social, economic and cultural aspects. In the state of Alagoas, the artisanal capture of shrimp is predominantly carried out by means of motorized vessels that use the double trawling technique. The municipality of Piaçabuçu is currently the main center of fishing production in the state. The activity of motorized artisanal fishing directed to marine shrimp has been taking place in Pontal do Peba, Piaçabuçu, Alagoas, since 1960. This activity plays an important role in the community, providing livelihoods and income for local artisanal fishers. However, the lack of attention on the part of the social and political segments responsible for planning the region in relation to this sector of the regional economy is remarkable. The objective of this study was to conduct a comprehensive analysis of the socioeconomic and environmental aspects related to shrimp trawling in Pontal do Peba, Piaçabuçu, Alagoas, Brazil. For this, qualitative and quantitative methods were used, such as interviews with the use of a semi-structured questionnaire, direct observations, photographic records and a field diary. The sampling technique adopted was Snowball Sampling, known as "snowball". Between June 2022 and January 2023, interviews were conducted with 43 fishermen. The fishing activity is artisanal in nature and is characterized by the involvement of the family. There was an exclusivity of men involved in the fishing activity itself, with the presence of women recorded only in the post-fishing stages. The general profile of the fishermen revealed a low level of education, a strong connection with the local fishing culture and a high dependence on fishing resources. Most respondents rely solely on fishing as a source of livelihood. Fisheries are carried out both during the day and at night and each trawl has an average duration of three hours. Fishermen work 8 to 12 hours a day, with an average of 10.6 hours (±1.4 hours). The majority of the interviewees (83.7%) stated that they do not own the vessels they use. The main form of conservation used during thefishery was ice. The results showed a high dependence of fishermen on middlemen. Among the environmental problems in the community, the fishermen cited: garbage disposal, lack of basic sanitation and turtle mortality. It was found that fishermen have varied environmental perceptions, while only (30.2%) recognize fishing as capable of causing impacts to the environment, most (69.8%) affirm that the activity is not capable of causing damage to the environment. Most fishermen (58.1%) reported noticing a significant decrease in the amount of shrimp caught in recent years. A significant group of interviewees (28.5%), despite understandingthe relevanceof the closure, believe that the established period is incorrect. Two main forms of processing have been identified for the shrimp caught: filleting and smoking. On the other hand, for the portion of fish of the accompanying fauna that is used, two techniques were mentioned: evisceration and salting-drying. The waste resulting from the processing of shrimp andfishis disposedof directly into the sea. In general, the need to include fishermen as active participants in decisions related to public policies aimed at the fishing sector, fisheries management and environmental conservation is highlighted.